Methodology in language teaching: an anthology of current practice - Richards, Jack C; Renandya, Willy A. (New York: Cambridge, 2002)
Sus temas principales son: Section 1.- Approaches to teaching, Section 2.- Lesson planning and classroom management, Section 3.- Classroom dynamics, Section 4.- Syllabus design and instructional materials, Section 5.- Task and projetec work
Incluye bibliografía
Keywords: Language English - Teaching